Positive alcohol expectancies mediate associations between ADHD behaviors and alcohol-related problems among college students - Elmore, Alexis; Nikolas, Molly; Canu, Will (Attention deficit and hyperactivity disorders, 2018)
An increasing percentage of college students report being affected by ADHD behaviors, and this population is at increased risk of experiencing negative consequences associated with alcohol consumption. However, specific factors motivating alcohol consumption and contributing to negative outcomes among these individuals are not well understood. Recent work suggests alcohol expectancies may interact with ADHD behaviors to influence negative drinking-related outcomes among those with elevated inattention and/or hyperactivity-impulsivity. Seven-hundred-forty emerging adults ( M age = 19.13 [SD = 2.25] years; 72.1% female; 85.8% Caucasian) enrolled in two public universities in the Southeast and Midwest USA completed the Brief Comprehensive Effects of Alcohol Survey (B-CEOA) and provided self-reports of ADHD symptoms and drinking-related outcomes. Multiple mediation analyses were conducted to evaluate effects of ADHD behaviors (i.e., hyperactivity-impulsivity, and inattention) and related impairment in major life domains (e.g., social interactions, occupational and educational activities, fulfillment of daily responsibilities) on drinking-related outcomes via positive and negative alcohol expectancies, controlling for sex, age, co-occurring oppositional behaviors, and data collection site. Inattention, hyperactivity-impulsivity, and impairment directly predicted both personal and social problems consequent to alcohol use. Effects of ADHD behaviors and impairment on drinking-related personal and social problems were partially mediated by positive expectancies. Findings are consistent with and extend prior work supporting a role of positive alcohol expectancies in alcohol-related negative outcomes among college students experiencing mild to moderate symptoms of ADHD.